Pemahaman Kader Korps PMII Putri (KOPRI) Komisariat Universitas Islam Negeri Sumatera Utara Terhadap Feminisme - Umaini, Riza (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2023)
This research uses a qualitative approach because it seeks to provide an in-depth description of the main problem of this study, namely the understanding of the KOPRI cadres of the UIN SU Medan commissariat towards feminism. While this type of research is philosophical research because the object studied is about the existence of feminism in student organizations. Thus this research is modeled on research on actual problems. The results of this study are: 1) Broadly speaking, the KOPRI cadre of the UINSU commissariat understands feminism as a collective work in which justice is spoken, and justice is the language of the world. So the variety of ideas in feminism does not mean that feminism contains utopian things and is full of fallacies. But as proof that women are able to formulate their ideas through their own experiences and can change the life of the world for the better. Thus, it can be concluded that the understanding of the KOPRI cadre of the UINSU commissariat is close to the understanding of moderate Islamic feminism. 2) The background of the formation of the understanding of KOPRI cadres of the UIN-SU Commissariat towards feminism begins with an awareness of their position and role as cadres, students, Muslims, and women. So that through this position they have accurate data related to feminism, while through this role they have the awareness to conduct a systemic empirical assessment of feminism, because feminism offers various analyses of the causes, perpetrators of women's oppression.Keywords: Comprehension, KOPRI, Feminism.